PENGARUH DISIPLIN KERJA, MOTIVASI, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA GUARDIAN GERAI UBUD PT HERO SUPERMARKET - Ni Made Dwi Lestari; I Wayan Mendra; Tjok Istri Sri Harwathy (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
Human Resources are an important asset in a company that must be improved effectively and efficiently in order to achieve quality performance to achieve company goals. One of the factors that can affect employee performance is work discipline, motivation, and job satisfaction. This study aims to determine the effect of work discipline, motivation, and job satisfaction on employee performance at the Guardian Gerai Ubud PT Hero Supermarket. The population in this study were 50 people. The sample in this study was the entire population at the Guardian Gerai Ubud PT Hero Supermarket. Determination of the sample in this study is Non Probability Sampling in which the chosen technique is saturated sampling (census). Saturated Sampling (census) is a sampling method when all members of the population are sampled. The analysis technique used is the Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, Multiple Correlation Analysis, Determination Analysis, t-test. The results of this study indicate that the variable work discipline has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, and job satisfaction has a positive and significant effect on employee performance at the Guardian Gerai Ubud PT Hero Supermarket